Design of a novel routing architecture for harsh environment monitoring in heterogeneous WSN. (12th October 2018) - Verma, Sandeep; Sood, Neetu; Sharma, Ajay Kumar
Abstract : Wireless sensor network (WSN) has proved to be a hardcore desideratum for the continuous monitoring of hostile areas suffering from devastating forest fires, sudden volcanic eruptions, floods and many more. It can be contemplated by reviewing the state‐of‐the‐art routing strategies, network instability and the delay incurred in data reception at the user end may lead to deplorable circumstances. In this study, a design of a novel routing architecture is proposed for harsh environment monitoring in heterogeneous WSN. It aims to ameliorate the stability period and network lifetime by shortening the communicative distance of nodes from the gateway node and by mitigating the hot‐spot problem in the network. This architecture comprises of a network with multiple gateway nodes (MGNs) (four in this case), placed at equidistant from each other, outside the monitoring area. MGN is enriched with unlimited resources of energy, computation and coverage capabilities. The proposed MGN‐based routing architecture (MRA) also improves the cluster head selection by incorporating node density factor along with energy and distance. Simulations show that MRA outperforms the state‐of‐the‐art protocols, i.e. threshold‐sensitive energy‐efficient delay‐aware routing protocol, Stable and Energy Efficient Clustering Protocol (SEECP), and Distance based Residual Energy‐Efficient Stable Election Protocol (DRESEP) for two different cases of 'nodes and energy' fractions at various performance metrics.